BIOCERAMIC-BASED ROOT CANAL SEALERS: A REVIEW - Aurelian Corneliu Cirstea; Lelia Mihaela Gheorghiță; Oana Andreea Diaconu; Marilena Bataiosu; Ruxandra Voinea Georgescu; Ionela Teodora Dascălu; Oana Elena Amza; Andreea Gabriela Nicola; Mihaela Raescu; Mihaela-Jana Tuculina (Romanian Society of Oral Rehabilitation, 2020)
The search for a perfect root canal obturation led to the develop of a new class of materials. Tricalcium silicat base sealer or bioceramic sealers are the answers to some problems that appeared with traditional warm obturation techniques. The aim of this review is to evaluate the new material based on literature findings. An extensive search of the endodontic literature was made to identify publications related to bioceramic-based root canal sealers. The properties, such as adhesion, biocompatibility, solubility, antimicrobial efficiency were evaluated in an laboratory manner. We have a lack of proper evaluation with in vivo studies, thus having an open for further studies.